Study of Sweating Rate and Microscopic Anatomy of Some Breeds Bulls Sweat Glands in Different Body Parts - Ita Wahju Nursita; Firmansyah Trisaputra; Nur Cholis; Heni Setyo Prayogi (Faculty of Animal Science, Universitas Brawijaya, 2022)
The study aimed to analyze the sweating rate and the microscopic anatomy of sweat glands of many breed bulls in different parts of the body. Ten bulls of 5 breeds (Simmental, Limousin, Crossed Ongole breed (PO), SimPO (Crossed between Simmental and PO), and LimPO (Crossed between Limousine and PO) in Authorized Slaughterhouse of Malang and Surabaya city were used during the study. Two bulls of each breed were observed for the sweating rate using a Cobalt Chloride Disk (CCD). The skin samples of four places in the legs and back of the animal were taken to be observed under a light microscope in the laboratory of Biosains of Universitas Brawijaya.Â The result showed that for all breeds, the sweating rates in the legs were higher (P<0.05) than in the back.Â It was observed that the sweat glands of the legs had tubular, but the back part is in irregular shapes. Based on the study result it is suggested to measure the sweating rate in the back part of the animal body.